The Role of Organizational Capacity in Student-Athlete Development - Andrassy, Emily J.; Svensson, Per; Bruening, Jennifer; Huml, Matt R.; Chung, Michael (Journal of Intercollegiate Sport, 2014)
In-depth interviews were conducted with the life skills coordinators of 9 of 21 institutions identified as being “dedicated” to service (Andrassy & Bruening, 2011). As a result of service being one portion of CHAMPS/Life Skills programming, we expanded our investigation to include all aspects of this student development program. In particular, we focused our inquiry on organizational capacity and its role in student involvement. Findings indicate these ‘dedicated’ athletic departments were characterized by strong organizational capacity for engaging student-athletes in meaningful service efforts. The critical role of coaches and mutual values among internal stakeholders emerged as the primary strengths of department’s human resources capacity. Despite the limited financial capacity, departments were able to creatively secure some funding for development programs. The ability to leverage external relationships, an organizational culture promoting participative decision-making and student-athlete development, and on-going efforts to improve service and life skills opportunities for student-athletes indicated strong structural capacity.